Distribution of indigenous strains of atoxigenic and toxigenic Aspergillus flavus and Aspergillus parasiticus in maize and peanuts agro-ecological zones of Kenya. Issue 1 (December 2015) - Okun, Daniel; Khamis, Fathiya; Muluvi, Geoffrey; Ngeranwa, Joseph; Ombura, Fidelis; Yongo, Moses; Kenya, Eucharia
Abstract Background Grains of important food and export crops in Africa are susceptible to contamination by toxin-producing moulds. Aflatoxins are mycotoxins associated with liver damage and cancer in humans and animals. These toxic substances are produced by fungi (such asAspergillus flavus andAspergillus parasiticus ) in food and feed exposed to poor conditions during crop cultivation, storage or processing of harvest. The presence of aflatoxins in especially maize and peanuts in Kenya is of great concern. Recent developments in the application of atoxigenic strains of these fungi as biological control agents against toxigenic strains could be a solution to the problem. The objective of this study was to isolate, identify and characterize atoxigenic and toxigenic strains ofA. flavus andA. parasiticus in Kenya, and investigate possible application of atoxigenic strains in control of aflatoxin levels in maize and peanuts. Fungal communities in soils of maize and peanut fields were examined to determine the distributions of aflatoxin-producingAspergillus species and to identify endemic atoxigenic strains. 220 isolates belonging toA. flavus andA. parasiticus were collected randomly from soils of maize and peanuts fields in seven agro-ecological zones and characterized using morphological and physiological examination. Results Aspergillus section Flavi was detected in all the 57 soil samples collected in Kenya. Members of Aspergillus section Flavi L strain was the most common (54 %), followed by S-strains (35 %). AmongAspergillus, A. flavus was the most predominant (63.2 %), followed byA. parasiticus (27.7 %), A. tamari (5.5 %) andA. nomius (2.7 %). The mean CFU of theAspergillus colonies per gram of soil was highly variable among the districts, ranging from 3.0 × 103 to 1.72 × 106 (p  < 0.05). The mean pH across the collection sites also varied according to the respective agroecological zones (pH 5.5–6.8) which is within the optimal pH requirement for the members of section Flavi. There was no significant variation in temperature across the sampling sites (p  > 0.05). The results also showed thatA. flavus was detected in all the zones examined. Conclusions Each of the regions had atoxigenic strains of potential value which can be employed as biological control agents in the management of aflatoxicoses.